Rethinking inclusive primary education: Managerial leadership, pedagogical strategies, and Islamic value-based practices in Indonesia - Intan Andriani Hasanah; Jamil Suprihatiningrum (Journal of Integrated Elementary Education, 2026)
Inclusive education at the elementary level is essential to ensure equal learning opportunities for all children, including those with disabilities. This study explores and interprets the implementation of inclusive primary education in an Islamic elementary school through an in-depth qualitative case study. Using an interpretative qualitative design, data were collected through classroom observations, in-depth interviews with school leaders and teachers, and document analysis to capture institutional practices and lived experiences within the school context. The findings reveal three interconnected dimensions shaping inclusive practice. First, transformative managerial leadership institutionalizes inclusive policies and fosters a collaborative school culture. Second, adaptive pedagogical strategies, including differentiated instruction, flexible assessment, and peer collaboration, support diverse learner needs in everyday classroom practice. Third, Islamic moral-spiritual values, including justice (‘adl), compassion (rahmah), and communal responsibility, provide an ethical foundation that strengthens inclusive commitments and relational engagement among stakeholders. Rather than positioning inclusion solely as a technical pedagogical reform, this study demonstrates how value-based leadership and religious moral frameworks can reinforce inclusive educational transformation. The study proposes an integrative perspective on inclusive education by linking contemporary inclusive pedagogy with Islamic moral-spiritual values in a primary school context.